When the post-revolutionary state decentralizes: the reorganization of political structures and administration in Mozambique - Elísio Macamo; Dieter Neubert (Cadernos de Estudos Africanos)
The authors of this article draw from an analyticalperspective which defines clientelism in Africa as a potential resource for political participation and accountability, in order to then discuss the logic of decentralization in Mozambique under the conditions of the economic and social failure of Frelimo's revolutionary project. Over the past fifteen years, since the introduction of a structural adjustment project under the auspices of the IMF and the World Bank, Mozambique has been attempting to dismantle its highly centralized political process against the background of an ever increasing influence of development aid on the functioning of state institutions.